Pengembangan Media Pembelajaran Soal cerita dengan Cerpen Pada Materi Operasi Hitung Campuran untuk Siswa Kelas IV SDN Sumberkerep Tahun Ajaran 2012/2013 - Laili, Nur Hidayati; Tristiana, Devy (saintis, 2016)
The purpose of this study was to develop learning media of story question with short story for the fourth graders of the state of elementary school of Sumberkerep on material of mixture arithmetic operations. The design of the study was the development of learning device according to Thiagarajan, the 4-D models consisting of four stages of development that Define, Design, Develop and Desseminate. In this study, the data obtained from the test students after using mathematical stories, charging student questionnaire responses, and the results of the validation. Based on the analysis, it was known that the results of the validation by the validator to the mathematics of short stories that was reaching a scale of 3.8 (valid), the results of the assessment practicality validator which states that short stories were developed can be applied math in elementary school, and the results of student questionnaire responses stating responses positive student reaches 95%. The results of student learning was said to be completed in accordance with KKM set at school. According to the results of this study concluded that short stories that have developed mathematical fit for use as a medium of studentsâ learning in solving arithmetic operation story material mixed views on the criteria valid, practical and effective.